Krüppel-like factor 5 remodels lipid metabolism in exercised skeletal muscle - Konstantin Schneider-Heieck; Joaquín Pérez-Schindler; Jonas Blatter; Laura M. de Smalen; Wandrille Duchemin; Stefan A. Steurer; Bettina Karrer-Cardel; Danilo Ritz; Christoph Handschin (Molecular Metabolism)
Regular physical activity induces a variety of health benefits, preventing and counteracting diseases caused by a sedentary lifestyle. However, the molecular underpinnings of skeletal muscle plasticity in exercise remain poorly understood. We identified a role of the Krüppel-Like Factor 5 (Klf5) in this process, in particular in the regulation of lipid homeostasis. Surprisingly, gain- and loss-of-function studies in muscle in vivo revealed seemingly opposite functions of Klf5 in the response to an acute exercise bout and chronic training, modulating lipid oxidation and synthesis, respectively. Thus, even though only transiently induced, the function of Klf5 is complex and fundamental for a normal long-term training response. These findings highlight the importance of this mediator of external stress response to adaptive remodeling of skeletal muscle tissue.